X ray photoelectron analysis of oxide-semiconductor interface after breakdown in Al2O3/InGaAs stacks - Shekhter, P. (2014)
In this work, the post-breakdown characteristics of metal gate/Al2O3/InGaAs structures were studied using surface analysis by x ray photoelectron spectroscopy. The results show that for dielectric breakdown under positive bias, localized filaments consisting of oxidized substrate atoms (In, Ga and As) were formed, while following breakdown under negative bias, a decrease of oxidized substrate atoms was observed. Such differences in the microstructure at the oxide-semiconductor interface after breakdown for positive and negative voltages are explained by atomic diffusion of the contact atoms into the gate dielectric in the region of the breakdown spot by the current induced electro-migration effect. These findings show a major difference between Al2O3/InGaAs and SiO2/Si interfaces, opening the way to a better understanding of the breakdown characteristics of III-V complementary-metal-oxide-semiconductor technology.